TWITTER AND POLITICAL PROPAGANDA IN THE 2019 ELECTIONS IN INDONESIA - Widayat, Rossi Maunofa; Nurmandi, Achmad; Rosilawati, Yeni; Nashir, Haedar (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia, as the world’s largest Muslim country, made the 2019 Elections as the starting point of the rise of Muslims in the national political scene. This paper aims to analyze the strategy of Islamic political party campaigns on Twitter in the 2019 Elections. This study employed a qualitative method. Nvivo 12 Plus Software was utilized for data analysis. The Ncapture feature was used to explore Twitter’s accounts @Official_PAN, @DPPP_PKB, @PKSejahtra, and @DPP_PPP for four months (January-April). This paper reveals that issues built-in political party propaganda were quite diverse. Parties supporting the government (PKB and PPP) tended to uncover the issues of successful development implemented by the government. Meanwhile, those opposing the government, such as PAN, highlighted the issues related to women and gender. PKS, as an opposition party, discussed the issues of the Bill on the protection of religious leaders, the abolition of motorcycle tax, and lifelong drivers’ license to counter government policies.